Personnel selection: a longstanding story of impact at the individual, firm, and societal level - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2020)
This paper discusses how and why the field of personnel selection has made a long-lasting mark in work and organizational psychology. We start by outlining the importance and relevance of the well-established analytical framework (criterion-related validity, incremental validity, utility) for examining the impact of selection at the individual (job performance) level. We also document the substantive criterion-related validities of most common selection procedures on the basis of cumulative meta-analytic research. Next, we review more recent research that investigated the impact of selection at the more macro organizational (firm performance) level. We show that the positive relationship between selection and performance at the individual-level translates to the organizational-level. Finally, we draw upon a longstanding project on situational judgement tests to exemplify the tradition of implementing interventions for improving the way selection is done in specific settings. We reflect on the reasons for this programme's impact on the selection process and its decision makers. We end with recommendations to researchers in personnel selection and other fields for increasing the impact of their research projects.